2022
DOI: 10.1101/2022.09.11.507456
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Basolateral amygdala astrocytes are engaged by the acquisition and expression of a contextual fear memory

Abstract: Astrocytes are key cellular regulators within the brain. The basolateral amygdala (BLA) is implicated in fear memory processing, yet most research has entirely focused on neuronal mechanisms, despite a significant body of work implicating astrocytes in learning and memory. In the present study, we used in vivo fiber photometry to record from amygdalar astrocytes across fear learning, recall, and three separate periods of extinction. We found that BLA astrocytes robustly responded to foot-shocks during acquisi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
1
0
0
Order By: Relevance
“…3b). A recent study using in vivo fibre photometry showed that astrocytes in the BLA are activated during acquisition and expression of contextual fear memory 44 , consistent with our observation that the astrocyte cell types are remodelled by fear memory consolidation (Fig. 3a and Extended Data Fig.…”
Section: Articlesupporting
confidence: 91%
“…3b). A recent study using in vivo fibre photometry showed that astrocytes in the BLA are activated during acquisition and expression of contextual fear memory 44 , consistent with our observation that the astrocyte cell types are remodelled by fear memory consolidation (Fig. 3a and Extended Data Fig.…”
Section: Articlesupporting
confidence: 91%